Human Herpesvirus 6A Is a Risk Factor for Multiple Sclerosis - Lundström, Wangko; Gustafsson, Rasmus (Frontiers in Immunology, 2022)
The role for human herpesvirus (HHV)-6A or HHV-6B in multiple sclerosis (MS) pathogenesis has been controversial. Possibly because the damage of the virus infection may occur before onset of clinical symptoms and because it has been difficult to detect active infection and separate serological responses to HHV-6A or 6B. Recent studies report that in MS patients the serological response against HHV-6A is increased whereas it is decreased against HHV-6B. This effect seems to be even more pronounced in MS patients prior to diagnosis and supports previous studies postulating a predomination for HHV-6A in MS disease and suggests that the infection is important at early stages of the disease. Furthermore, HHV-6A infection interacts with other factors suspected of modulating MS susceptibility and progression such as infection with Epstein-Barr virus (EBV) and Cytomegalovirus (CMV), tobacco smoking, HLA alleles, UV irradiation and vitamin D levels. The multifactorial nature of MS and pathophysiological role for HHV-6A in inflammation and autoimmunity are discussed.